2014
DOI: 10.2478/v10129-011-0076-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Tests for Identification and Characterization of Tomato Cultivars

Abstract: Various chemical tests are being used to reveal chemical differences among the seeds or seedlings of different cultivars. Study to characterize and identify 24 tomato cultivars based on chemical test chemicals viz., Standard phenol test, Modified phenol test, NaOH test, KOH test and Seedling growth response to added chemicals reveled that, most of the cultivars studied were distinct from other cultivars. No single chemical test could distinguish all the varieties. However, distinguishable chemical characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Walls ( 1965 ), reported that the phenol colour reaction depends on the quality and quantity of oxidases present in the seeds, whereas Takahashi and Hamza ( 1983 ), reported that monophenol oxidase was extremely localized in aleurone layer of grains even though it is present in all other plant parts of a variety. Presence of enzyme system has been utilized to distinguish the crop varieties in rice and tomato (Pieper 1922 ; Joshi and Banerjee 1970 ; Mansing 2010 ; Vijayalakshmi and Vijay 2009 ; Anitalakshmi et al 2014 ; Sripunitha and Sivasubramaniam 2014 ; Vishwanath et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Walls ( 1965 ), reported that the phenol colour reaction depends on the quality and quantity of oxidases present in the seeds, whereas Takahashi and Hamza ( 1983 ), reported that monophenol oxidase was extremely localized in aleurone layer of grains even though it is present in all other plant parts of a variety. Presence of enzyme system has been utilized to distinguish the crop varieties in rice and tomato (Pieper 1922 ; Joshi and Banerjee 1970 ; Mansing 2010 ; Vijayalakshmi and Vijay 2009 ; Anitalakshmi et al 2014 ; Sripunitha and Sivasubramaniam 2014 ; Vishwanath et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…These tests were similar to observations in soya bean (Roopa et. al., 2008) and tomato (Vishwanath et. al., 2013).…”
Section: Seedling Growth Response To Kinetinmentioning
confidence: 99%
“…Similarly, in the case of Tomato, chemical tests are used to identify and characterize different cultivars. Though no single chemical test could distinguish all the varieties distinguishable chemical characters were used to develop the keys for the identification of each cultivar (Vishwanath et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate identification of varieties is not only a pre requisite for DUS testing, but is critical for the production of quality seed also. The most common method of varietal identification is grow out test [3,4], which is based on the morphological markers at various growth stages of plant, however it has many disadvantages such as interaction with environment, high cost and lengthy time required, low polymorphism in closely related varieties which were bred by using elite lines". "The time duration of one complete season for identification of varieties using standard grow-out test is one of the major constraints in its implementation, particularly in the major rice growing regions of North Western Himalayas.…”
Section: Introductionmentioning
confidence: 99%